Data on Swiss consumers’ perception of different types of sustainability levies, agriculture and willingness to choose suboptimal potatoes in different settingsZenodo - Jeanine Ammann; Gabriele Mack; Rita Saleh (Data in Brief)
We present representative survey data from 481 Swiss consumers. Data were collected in the German-speaking parts of Switzerland in February and March 2024. The survey includes three independent main parts.In a first part, we collected qualitative and quantitative data on participants’ perception of Swiss agriculture and farmers. Specifically, participants’ trust in crop and livestock production farmers and their perceived knowledge about production methods and their affect towards farmers was assessed.In a second part, we collected quantitative data on participants’ preference for different sustainability levies. For this, six different products were used (i.e., fresh/processed vegetables, dairy, and meat). For each of these six products, participants were shown four levy options from which they had to choose the one that they found most appealing. For vegetables, the options were: (A) reduction of risks related to plant protection products, (B) more support for local farmers, (C) support for environmental sustainability, and (D) sustainability projects in general. For the animal products, option (A) was an increase in animal welfare, whilst options (B), (C) and (D) were the same as for the vegetable products.In a third part, we collected qualitative and quantitative data on participants preferences for suboptimal or optimal potatoes. Here, a 2 × 2 experimental design (setting × information) was used. This means that participants were presented with either a supermarket or farm shop setting and with or without food waste information. Participants then chose between two potatoes: optimal potato A, suboptimal potato B, or neither. Both potatoes were equally expensive.Further, we collected personal information about participants such as gender, age, education level and how they placed themselves regarding their political orientation on a left-right scale. We further collected behavioural data including diet, that is, milk and meat consumption frequency as well as shopping behaviour, where we asked participants where they usually did their grocery shopping. At the end of the survey, we used existing and new scales to measure participants’ perception of farmers, health consciousness and environmental attitudes. Before collecting this data, ethical approval was obtained from the Agroscope ethical commission (application EK-AGS-2024-N-01).